Concurrence of tax and criminal sanctions in the light of the Convention for the Protection of Human Rights and Fundamental Freedoms - Paweł Majka (Prawo Budżetowe Państwa i Samorządu)
This paper analyses an applicability of a rule not to be punished twice in case of the concurrence of tax and criminal sanctions. The Author studied limits of legislator’s power to set the regulations connected with concurrence of tax and criminal sanctions and limits established by international law. In the Author’s opinion the main barriers in establishing such limits arise from the Convention for the Protection of Human Rights and Fundamental Freedoms and judgments of the European Court of Human Rights.